Fronto-temporal disconnectivity and symptom severity in children with autism spectrum disorder - Poustka, Luise; Henze, Romy; Haffner, Johann (The world journal of biological psychiatry, 2012)
Objectives. There is increasing evidence that many of the core behavioural impairments in autism spectrum disorders (ASD) emerge from disconnectivity of networks that are important for social communication. The present study aimed at investigating which specific fibre tracts are impaired in ASD and if possible alterations of white matter are associated with clinical symptomatology. Methods. Eighteen children with ASD and 18 carefully matched typically developing controls aged 6-12 years were examined using diffusion tensor imaging (DTI) and voxel-based morphometry (VBM). Fractional anisotropy (FA) values were correlated with symptom severity as indexed by the children's scores on the Autisms Diagnostic Observation Schedule (ADOS) and the Autism Diagnostic Interview-Revised (ADI-R). Results. Decreased FA values were identified for the fornix (FO), the superior longitudinal fasciculus (SLF) the corpus callosum and the uncinate fasciculus (UF) in the ASD group compared to controls, with most prominent differences in the UF bilaterally and the right SLF. FA values of affected fibre tracts were negatively associated with clinical measures of autistic symptomatology. We did not observe significantly altered grey or white matter concentration after correction for multiple comparisons. Conclusion. Our findings support the hypothesis of abnormal white matter microstructure of fronto-temporal cortical networks in ASD, which are associated with core symptoms of the disorder.